Upaya Penanggulangan Perubahan Iklim Melalui Pengolahan Limbah Buah dan Sayur Menjadi Ekoenzim Di Desa Wonosoco, Kabupaten Kudus - Farida Yuliani; Fazat Fairuzia; Hendy Hendro; Wahid Nurfajri; Muhammad Imanuddin (Institut Pertanian Bogor, 2025)
The training in this community service activity aimed to improve the knowledge and skills of the Wonosoco Village community to overcome organic waste and reduce the percentage of organic waste disposal in the final disposal site (TPA) through the processing of organic waste from fruits and vegetables into ecoenzymes. This activity is carried out through direct practical activities in several stages: analysis of community needs, activity design, delivery of materials, manufacture and application of ecoenzymes, and evaluation of activities. The training provided to PKK and farmer groups increased community knowledge of ecoenzyme knowledge by 95.24%. The benefits of ecoenzymes in the fields of agriculture and plantations as complementary nutrients for fertilizers and as cleaning materials for household appliances and the processing of vegetable and fruit waste were 96.67%. Knowledge about the economic potential of ecoenzymes increased by 100%. This organic waste processing training can also change community attitudes toward waste management to reduce the effects of greenhouse gases, as indicated by the percentage of behavior of disposing of organic waste directly in the trash from 67% down to 0% and switching to 85% to be processed into fertilizer or ecoenzymes and 15% given to livestock.